Wogonin induces ferroptosis in pancreatic cancer cells by inhibiting the Nrf2/GPX4 axis - Liu, Xing; Peng, Xinhui; Cen, Shuai; Yang, Cuiting; Ma, Zhijie; Shi, Xinyuan (Frontiers in Pharmacology, 2023)
Pancreatic cancer is a common gastrointestinal tract malignancy. Currently, the therapeutic strategies for pancreatic cancers include surgery, radiotherapy, and chemotherapy; however, the surgical procedure is invasive, and the overall curative outcomes are poor. Furthermore, pancreatic cancers are usually asymptomatic during early stages and have a high degree of malignancy, along with a high rate of recurrence and metastasis, thereby increasing the risk of mortality. Studies have shown that ferroptosis regulates cell proliferation and tumour growth and reduces drug resistance. Hence, ferroptosis could play a role in preventing and treating cancers. Wogonin is a flavonoid with anticancer activity against various cancers, including pancreatic cancer. It is extracted from the root of Scutellaria baicalensis Georgi. In this study, we show that wogonin inhibits the survival and proliferation of human pancreatic cancer cell lines and induces cell death. We performed RNA-sequencing and analysed the differentially expressed gene and potential molecular mechanism to determine if wogonin reduced cell survival via ferroptosis. Our results showed that wogonin upregulates the levels of Fe2+, lipid peroxidation and superoxide and decreases the protein expression levels of ferroptosis suppressor genes, and downregulates level of glutathione in pancreatic cancer cells. In addition, ferroptosis inhibitors rescue the ferroptosis-related events induced by wogonin, thereby confirming the role of ferroptosis. A significant increase in ferroptosis-related events was observed after treatment with both wogonin and ferroptosis inducer. These results show that wogonin could significantly reduces pancreatic cancer cell proliferation and induce ferroptosis via the Nrf2/GPX4 axis. Therefore, wogonin could be potentially used for treating patients with pancreatic cancer.